Teachers as Researchers: An Emphasis on the Readiness and Attitude towards Action Research - Jr, Leo L. Codilla; Barot, Hannah Yangson- (International Journal of Membrane Science and Technology, 2023)
This study explored the readiness and attitude of teachers in conducting action research. Specifically, the study aimed to determine the profile of the teachers, the level of the participants’ research readiness, the extent of the participant’s attitude toward action research, and the factors that hinder the participants in conducting action research. The study employed a descriptive-correlational research design. Frequency counts, percentages, weighted mean, one-way ANOVA, and Pearson product-moment correlation were used in the study. Results revealed that the participants had a relatively high level of education and experience in teaching, but their research involvement was limited. The participants were motivated to conduct action research, but their research literacy and analysis skills needed improvement. In addition, the study highlighted the need for support from various stakeholders to equip teachers with the necessary knowledge and skills to conduct action research effectively. The hindering factors to conducting action research were overburdened work schedules, lack of fundamental skills, and inadequate training and experience. Several factors, including research outlook, research interest, research benefit, research motivation, research literacy, research support, and research analysis and interpretation, were found to have a strong positive correlation with research readiness. It is recommended that teachers may be provided more training, support, and resources for them to increase their research involvement and strengthen their readiness and positive attitude toward action research.